KORELASI NILAI MATA KULIAH PERSYARATAN SKRIPSI DAN JUMLAH TATAP MUKA BIMBINGAN SKRIPSI TERHADAP KELANCARAN PENYELESAIAN SKRIPSI MAHASISWA PG PAUD UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Yuki Widiasari; Melati Ismi Hapsari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
Fluently of writing thessis is influenced by many factors, such as: how to understand early childhood probleme, student’s competence in writing, how to understanding ressearch methods, and conselling process. The problem of this ressearch is accounting how much correlate value between score of subject matter and frequencies of conselling to fluently of writing the thessis. This ressearch is used quantitative methodes to analize, correlation. Outcome of this ressearch showed that values of correlation between score subject ‘persiapan skripsi’and times what needed to finished thessis is the biggest than the other (- 0,412) and values of correlation between statistics subject and times what needed to finished thessis is the smallest than the other (-0,362). Keywords: score of subject matter, time to finished the thessis